Intergenerational Transfer of Knowledge and Skills Among Rattan Entrepreneurs in Trangsan, Baki, Sukoharjo - Andhika Septiana*; Nurhadi Nurhadi; Saifuddin Zuhri (Riwayat: Educational Journal of History and Humanities, 2024)
This research discusses the knowledge transfer process carried out by rattan entrepreneurs in Trangsan, Baki, and Sukoharjo. This research uses a qualitative research method with a descriptive research design. Data collection methods used in research include interviews and observation. The result of this research is that the process of transferring knowledge of rattan entrepreneurs occurs between generations or from generation to generation. In knowledge transfer activities, there are four stages: Initiation or the beginning of knowledge being formed, then Implementation, namely the passage of knowledge from producers to successors. Then, at the ramp-up level, the successors started to use the knowledge he had gained. Then, the Integration stage is a form of knowledge satisfaction obtained by business successors. In the research, the main obstacle was found to be that providing knowledge requires quite a long time and a long experience due to various factors from the knowledge provider and the readiness of the transfer recipient to receive the knowledge.